EDUCATION THEORY AND EDUCATION SCIENCES APPLIED TO THE CRIMINOLOGY: A RENEWAL PROPOSE - Hikal Carreón, Wael (2019)
In the interest of various authors shown during reading, it will be noted that the work of articulation between the general theory of education and criminology, already has history. These work is resumed here to apply them mainly to areas of opportunity in pedagogical criminology and educational criminology, highlighting processes that can be improved for a renewal in educational chores, ways to teach, and research. In the beginning, the scientific, philosophical and projective dimensions of education are briefly adapted to criminology, this gives rise to continue the theme of improvement in educational criminology and pedagogical criminology, contextualizing the processes of the general theory to these others. Finally, the importance of the social work of criminology and its professionals, when expected, is highlighted, to provide knowledge to state agents who are in need of understanding the criminal problem, to determine public policy.